Methodology for selection of samples from borehole probe for technological characterization of iron ore - Santos,Gésner J. I. dos (2014)
The risks in the evaluation of mining projects are directly related to the probability of errors in the estimates, and, as the estimates are based on sampling results, this activity must be performed in a careful and planned way, to prevent surprises at the beginning of operation. To validate the representativeness of the borehole samples selected for the mineral processing studies, the geological resources evaluation team proposed a methodology based on the utilization of statistical analyses that, beyond considering the spatial distribution of the samples in the deposit, also assessed if they are representative of the populations under investigation. With this data, the geologist is able to make a fast analysis of the sampling's representativeness.